2018
DOI: 10.1016/j.spasta.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical estimation and prediction for censored responses

Abstract: Spatially-referenced geostatistical responses that are collected in environmental sciences research are often subject to detection limits, where the measures are not fully quantifiable. This leads to censoring (left, right, interval, etc), and various ad hoc statistical methods (such as choosing arbitrary detection limits, or data augmentation) are routinely employed during subsequent statistical analysis for inference and prediction. However, inference may be imprecise and sensitive to the assumptions and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Goovaerts (1999) reported that when the phenomena studied is complex, classical statistics are quickly abandoned in favor of the geostatistical models. Geostatistical data modeling has now virtually permeated all areas of oceanography, cartography, meteorology, agriculture, fisheries resources, civil engineering, finance (Ordoñez et al, 2018) as well as the environment, especially for the rehabilitation of contaminated soils (Lin et al, 2016, Shen et al, 2017, Xie et al, 2011. During the past years, significant effort have been invested to improve the characterization of contaminated soils and to reduce the costs related to the rehabilitation of these sites by applying geostatistical techniques within the characterization phase.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Goovaerts (1999) reported that when the phenomena studied is complex, classical statistics are quickly abandoned in favor of the geostatistical models. Geostatistical data modeling has now virtually permeated all areas of oceanography, cartography, meteorology, agriculture, fisheries resources, civil engineering, finance (Ordoñez et al, 2018) as well as the environment, especially for the rehabilitation of contaminated soils (Lin et al, 2016, Shen et al, 2017, Xie et al, 2011. During the past years, significant effort have been invested to improve the characterization of contaminated soils and to reduce the costs related to the rehabilitation of these sites by applying geostatistical techniques within the characterization phase.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this paper, we introduced a spatiotemporal linear model for censored and missing responses, extending the recent proposals by Lachos et al (2017) and Ordoñez et al (2018), which consider the estimation and diagnostics of spatial censored linear models. To obtain the ML estimates of model parameters, we developed a stochastic approximation of the EM algorithm, called the SAEM algorithm, leading to more efficient ML estimation than in the MCEM algorithm.…”
Section: Discussionmentioning
confidence: 92%
“…However, full conditionals for u 0,t , u 1,t are available and full MCMC is necessary only for z t . In order to fit larger data sets with this model, a promising direction of research to achieve approximate but faster computation is the use of Stochastic Approximation EM (SAEM, Jank (2006), Ordoez et al (2018)), which relies on a Taylor approximation of the Q function.…”
Section: Discussionmentioning
confidence: 99%